CLASSIFICATION OF THE STAGES OF DOMESTIC TELEVISION BROADCASTING DEVELOPMENT - A. B. Makushin (Вестник Кемеровского государственного университета, 2014)
Prompt development of information technologies forces experts in the field of mass media regularly to analyze the state of the Russian teleproduction. The paper is devoted to research of domestic telecasting stages for the purpose of carrying out analogy in approaches to production of modern television news formats.